1995
DOI: 10.1016/0029-7844(94)00342-b
|View full text |Cite
|
Sign up to set email alerts
|

Transumbilical placement of the vaginal probe in obese pregnant women

Abstract: Transabdominal ultrasonography in obese pregnant women is often unsatisfactory because of the poor transmission of ultrasound through a thickened abdominal wall. We report our experience with the placement of a transvaginal probe in the umbilicus to improve resolution in obese pregnant patients. The technique, which involves filling the umbilicus with ultrasound transmission gel and inserting the transvaginal probe into the umbilicus, was applied in 25 consecutive obese patients who had unsatisfactory fetal im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 1 publication
2
22
0
2
Order By: Relevance
“…However, the association between obesity and postponed EDD did not change over the study period. The use of harmonic imaging and a transumbilical approach, recommended for use in obese women 26 , may also have varied between sonographers.…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between obesity and postponed EDD did not change over the study period. The use of harmonic imaging and a transumbilical approach, recommended for use in obese women 26 , may also have varied between sonographers.…”
Section: Discussionmentioning
confidence: 99%
“…Very frequently incomplete cardiac examinations are cited as a reason for incomplete fetal surveys. Of the 19 complete cardiac examinations that were performed in this study, 18 became possible with the transumbilical approach and the overall visualization of organ systems was improved in 24 of the 25 (96%) cases (14).…”
Section: The Use Of Ultrasonography In Obese Gravidasmentioning
confidence: 99%
“…13 However, sonographic visualization of fetal structures is adversely affected by the size of the body fat layer and thus the degree of maternal obesity. 14,15 The impact of obesity on the quality of prenatal ultrasound examination was described by Wolfe et al, 16 in 1990, who found a greater risk for suboptimal visualization only when body mass index (BMI, kg/m 2 ) was above the 90th percentile. Although this finding (a decreased ability to visualize fetal structures with maternal obesity) was described over 14 y ago, quantification of this effect based on the severity of obesity using National Institute of Health (NIH) guidelines 17 is not well defined.…”
Section: Introductionmentioning
confidence: 99%